Efeito dos parâmetros experimentais utilizados na técnica volumétrica realizada em um aparato do tipo Sieverts nas medidas das propriedades termodinâmicas de formação de hidretos metálicos - Santiago, Matheus Henrique Ambrósio (Universidade Federal de São Carlos, 2024)
The volumetric technique performed in a Sieverts apparatus is used to study the hydrogen absorption behavior of a metal-hydrogen system. The technique’s resulting Pressure-Composition-Temperature diagrams reveal important properties about hydrogen storage and the formation of metal hydrides. To investigate the effect of experimental parameters and their associated errors on determining the thermodynamic properties of hydride formation, 12 experiments were conducted at four different temperatures. The experiments involved varying the volume of the apparatus reservoir and the mass of palladium, the chosen metal due to its excellent hydrogen storage properties and well-documented values in the literature. The obtained diagrams revealed experimental errors related to the applied hydrogen pressure dose at each step, the time between steps, and limitations of the equipment. Increasing the sample mass showed a displacement of the miscibility gap to higher values of absorbed hydrogen content, along with a slight tilt in the equilibrium plateau. On the other hand, increasing the reservoir volume resulted in a shift of the miscibility gap to lower values. While the results align with the literature, variations in volume and mass impacted thermodynamic properties (enthalpy and entropy of hydride formation) proportionally during absorption, but with opposing effects: volume increase made enthalpy and entropy values less negative, while mass increase made them more negative. During desorption, the effect of volume increase was more pronounced, making the values considerably more negative, while mass increase slightly reduced the negativity. Future investigations are necessary to verify results reproducibility and comprehend these effects on thermodynamic properties.
Effect of experimental parameters used in the volumetric technique performed in a Sieverts-type apparatus on measurements of the thermodynamic properties of metal hydride formation
Keywords: Armazenamento de hidrogênio; Hidreto metálico; Paládio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::PROPRIEDADES FISICAS DOS METAIS E LIGAS